2012
DOI: 10.1007/s12519-012-0379-8
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted MRI for detection and differentiation of musculoskeletal tumorous and tumor-like lesions in pediatric patients

Abstract: DWI shows promising results for determination of biological dignity in musculoskeletal tumors. Mean ADC ≤1.03×10(-3) mm(2)/s is a strong indicator of malignancy at the first diagnosis. The use of DWI for early diagnosis of tumor recurrence in comparison with standard MRI sequences should be evaluated in prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 17 publications
2
34
0
2
Order By: Relevance
“…Previous studies investigated the role of DWI in this field but a clear cutoff value of ADC to differentiate benign from malignant spinal tumors remains ambiguous . Perhaps this is due to the heterogeneity of tumor subtypes as well as variability in the protocols used .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies investigated the role of DWI in this field but a clear cutoff value of ADC to differentiate benign from malignant spinal tumors remains ambiguous . Perhaps this is due to the heterogeneity of tumor subtypes as well as variability in the protocols used .…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps this is due to the heterogeneity of tumor subtypes as well as variability in the protocols used . Neubauer et al, Pekcevik et al, and Ginat et al stated that an mADC value of 1.03 × 10 −3 mm 2 /s, 1.37 × 10 −3 mm 2 /s, and 1.01 × 10 −3 mm 2 /s, respectively, are reliable cutoff values to identify malignant musculoskeletal tumors. However, those authors found overlap of mADC values between benign and malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In this group of tumors with a wide variety of histologic types, when ADC selection was adapted to the lesion morphology, the diagnostic performance was only slightly inferior to that reported for the differentiation between retroperitoneal fibrosis and malignant tumors [26]. DWI seems to perform better for the evaluation of pediatric soft-tissue tumors, with reported sensitivity and specificity values of more than 90% [27]. The great histologic diversity of soft-tissue tumors in adults may account for these differences [20].…”
Section: Dwi Characterization Of Nonfatty Soft-tissue Lesionsmentioning
confidence: 76%
“…According to our own experience with extracranial DWI, inflammatory and oedematous soft tissue lesions present with a relatively stereotypic increase in ADC ranging from 1.4 to 2.6 [4]. ADC values < 1.0 measured in osseous or soft tissue lesions are characteristic of malignant tumours with high cellularity, abscess und some classical findings, such as epidermoid tumours [5]. In the presented case, increasingly high intramuscular signal on DWI at high b-values with corresponding low ADC values was the earliest diagnostic indicator of malignancy.…”
Section: Discussionmentioning
confidence: 99%